Acoustoelectric effect in semiconductor superlattice - Alok, Ujjwal; Kumar, Manoj; Singh, BK; Kumar, Praveen (BIBECHANA, 2012)
Acoustoelectric effect in semiconductor superlattice (SL) in the region ql >>1 has been studied. The equation of motion of the lattice has been transformed into a simple form which becomes identical with the dynamic equation for the wave amplitude in the theory of plasma turbulence. A dispersion relation has been derived from the acoustoelectric current J on the constant electric field E. It is noted that when the electric field is negative the current J rises, reaches a peak and falls off. On the other hand, when the electric field is positive the current decreases, reaches a peak and then rises. A similar observation has been noted for an acoustoelectric interaction in a multilayered structure resulting from the analysis of the Si/SiO2 structure. Keywords: acoustoelectric current; acoustomagnetothermal effect; quantum transparency DOI: http://dx.doi.org/10.3126/bibechana.v8i0.5013 BIBECHANA 8 (2012) 67-72